Black box: away from the stream of consciousness, or Why knights cry - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the analysis of the search for expressive means that were undertaken in the framework of knightly literature of the Middle Ages. Four directions of searching for the language of love are revealed, namely: in the tradition of the alba song, in the tradition of the chivalrous romance, in the tradition of the allegorical novel and in the tradition of curtuse poetry.
Keywords: medieval literature; language of love; search for expressive means; alba; chivalrous romance allegorical literature; symbolism; courtly universum